Chemical Prophylaxis And Antibiodiagram Of Tabernaemontana Divaricata (L) Leaves Against The Causative Organisms Of Bovine Mastitis Isolated From Clinical And Sub Clinical Samples - GOPINATH.S.M; SUNEETHA.T.B; MRUGANKA V.D; DAYANANDA.K.S.; ANANDA.S (International Journal of Pharma and Bio Sciences, 2012)
Phytochemical analysis of the dried leaves of Tabernaemontana divaricata (L). (Apocynaceae) indicated the presence of steroids, tannins, saponins, gums and reducing sugar. The pharmacological interest of these compounds coupled with the use of this plant in traditional medicine prompted to check for its antibacterial activity against causative organisms of Bovine Mastitis. Ethanol, methanol and aqueous extracts were found to possess maximum potency against infectious pathogens Staphylococcus aureus, Coagulase negative Staphylococcus aureus Streptococcus agalactae, Streptococcus uberis and Escherichia coli isolated locally from clinical and sub clinical samples of Mastitis from Karnataka region. The zone of inhibition and minimum inhibitory concentration of the extracts were found to be significant.